خصائص المنظومة المحاسبية الجيدة بحث تطبيقي على الوحدات الاقتصادية العاملة في مدينة مصراته (Economic studies journal, 2018)
The research aims to provide a reasonable level of confidence, knowledge, and familiarity with the technical aspects of the accounting systems. Which must be provided by the accountant to the designer of these systems, and follow up their implementation and operation later. So this research aims to achieve the integration of two main important science, accounting and computer.As a theoretical aspect, research was conducted on the available books specialized in the fields of accounting, computer and accounting information systems. The Questionnaire method was also used to obtain more information derived from the practical reality of selected sample members of the research community.The research reached a number of results. The most important of which is that the design stage of the systems is very important in drawing the overall plan of the system's work. In which it determines what the systems can achieve the objectives and benefits that have a marked impact on performance, accuracy, speed and cost reductionThe research recommends that the economic units should owning the advanced accounting systems, and to use the specialists in the fields of accounting and computer in the design of these systems. Also, the research recommends that the system should be analyzed and disaggregated according to the steps of the accounting cycle and provide the requirements and characteristics of each stage separately. This is to get the full accounting system Effectively and useful in achieving several goals and at various levels.
Keywords: المنظومة المحاسبية; الوحدات الاقتصادية; مدينة مصراته